Context and Catholicity in the Science and Religion Debate : Intercultural contributions from French-speaking Africa - Bom, Klaas, (Theology and Mission in World Christianity;, 2020)
For years the fact that the debate on science and religion was not related to cultural diversity was considered only a minor issue. However, lately, there is a growing concern that the dominance of 'Western' perspectives in this field do not allow for new understandings. This book testifies to the growing interest in the different cultural embeddings of the science and religion interface and proposes a framework that makes an intercultural debate possible. This proposal is based on a thorough study of the 'lived theology' of Christian students and university professors in Abidjan, Kinshasa and Yaoundé. The outcomes of the field research are related to a worldwide perspective of doing theology and a broader scope of scholarly discussions.